The prevalence of low birth weight and its associated maternal factors among women of reproductive age who gave birth to live babies within five years preceding the survey in Tanzania: an analysis of data from the 2015-16 Tanzania Demographic and Health Survey and Malaria Indicators Survey - Glorialoveness S. Lyimo; Fabiola Vincent Moshi (BMC, 2024)
Abstract Background Infant survival is an important factor in any community's health. Low birth weight affects babies not only during their infancy but also has long-term consequences for their health as adults. Unfortunately, Sub-Saharan Africa as a region is still dealing with the burden of Low birth weight (LBW), and Tanzania as a part of this region is no exception. So this study aimed to determine the Magnitude of Low Birth Weight and Its Associated Maternal Factors among Women of Reproductive Age who gave birth to live babies. Methods The study used analytical cross-sectional study design to analyze secondary data from the Tanzania Demographic and Health Survey and Malaria Indicators Survey 2015-2016. A total of 4,644 women of reproductive age who gave birth to live babies within five years preceding the survey were included in the study. Both bivariate and multivariable logistics regression analyses were used to assess maternal factors associated with low birth weight. Results The prevalence of LBW was 262(6.2%). After adjusting for confounders, the maternal factors associated with LBW were Age group of a pregnant woman [Less than 20 years (aOR = 1.907 CI = 1.134-3.205) in reference to those aged more than 34years], Number of ANC visits made [Inadequate visits (aOR = 1.612 CI = 1.266-2.05)], parity [para 2-4 (aOR = 0.609 CI = 0.453-0.818), para 5+ (aOR = 0.612 CI = 0.397-0.944)] and area of residence [Unguja (aOR = 1.981 CI = 1.367-2.87). Conclusion The prevalence of low birth weight in Tanzania remains high. Women's age, parity, number of Antenatal care visits (ANC), and area of residence were found to be maternal factors associated with LBW. Thus, early prenatal diagnosis of risk factors for low birth weight in high-risk pregnant women may help to reduce the LBW burden in Tanzania and its detrimental effects.